PROFESSIONAL METHOD TALKS TO ASSIST ESL TEACHERS IN MASTERING THEIR QUALIFICATIONS (American Journal of Research in Humanities and Social Sciences, 2023)
The present research experimentally studies the method related problems in ESL teachers in Uzbekistan and randomly compares their teaching techniques. The purpose of this research is to provide instructors with practical assistance to have productive teaching methods and time management in order to help them succeed in their professional growth. Furthermore, by asking secondary school ESL teachers in various ways, the school observation identifies several issues in the teaching process. The study will build on current influence research, assisting EFL teachers to teach school pupils by arranging "method talks" and recognizing and addressing students' learning challenges.